The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1974
DOI: 10.1111/j.1600-0773.1974.tb00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manganese on Enzymes in Rat Brain

Abstract: Rats were given MnCl2.4H2O (8 mg/kg) intraperitoneally daily for 120 days, and then sacrificed by decapitation. The brain was removed and dissected into three regions; cerebral cortex, cerebellum and remainder of the brain. Enzymic studies were conducted in these regions and compared with control animals. The activities of acetyl choline esterase and adenosine deaminase were significantly reduced in all the three regions. The activity of monoamine oxidase was increased in the cerebellum while the activity of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 16 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…The results are contradictory to those of Liapi et al (2008) and in agreement with Deskin et al (1981), Lai et al (1981, 1982), Martinez and Bonilla (1981) and Sitaramayya et al (1974). Deskin et al (1981) reported that AChE activity was significantly reduced in the striatum of rats treated with MnCl 2 (20 μg/g body weight/day), administered by oral gavage from birth to day 24 post-partum .…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The results are contradictory to those of Liapi et al (2008) and in agreement with Deskin et al (1981), Lai et al (1981, 1982), Martinez and Bonilla (1981) and Sitaramayya et al (1974). Deskin et al (1981) reported that AChE activity was significantly reduced in the striatum of rats treated with MnCl 2 (20 μg/g body weight/day), administered by oral gavage from birth to day 24 post-partum .…”
Section: Discussionsupporting
confidence: 59%
“…Deskin et al (1981) reported that AChE activity was significantly reduced in the striatum of rats treated with MnCl 2 (20 μg/g body weight/day), administered by oral gavage from birth to day 24 post-partum . Sitaramayya et al (1974) reported a significant decrease of AChE activity in the cerebral cortex, cerebellum and the remaining cerebral tissue in rats treated with MnCl 2 inoculated intraperitoneally for 120 days. In contrast, Liapi et al (2008) reported a significant increase of the activity of AChE in rats’ whole brains treated daily with MnCl 2 50 mg/Kg for 7 days by the i.p.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation